Advantages and challenges of using mobile ethnography in a hospital case study: WhatsApp as a method to identify perceptions and practices - Thomas Bjørner; Morten Schrøder (Qualitative Research in Medicine & Healthcare)
The focus of this article is to provide the reader with reflexivity and a framework for using mobile ethnography. Based on a case study with an ethnographic approach (including mobile ethnography using WhatsApp), we identified perceptions and practices for improved workflows and procedures related to nurses’ introduction and implementation of self-catheterization at the National Spinal Injuries Centre in Great Britain. We offer detailed procedures, advantages, and challenges in using mobile ethnography. The ethnographic approach consisted of four phases, including initial workshops, go-along observations, interviews, and a mobile ethnographic approach using WhatsApp as a mobile diary for six nurses. Within the case study, three major themes were revealed by the ethnographic approach, with the conclusion that nurses have positive attitudes towards self-catheterization, but these nurses are becoming less influential and the practices around this technique are consequently disappearing. The main result is that use of WhatsApp as a self-tracking tool can extend the methodological toolbox, but reflexivity and preliminary work are required to make the practice beneficial.